1990
DOI: 10.1002/j.1552-4604.1990.tb03569.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerance, and Pharmacokinetics of Cefepime Administered Intramuscularly to Healthy Subjects

Abstract: Steady state pharmacokinetics, absolute bioavailability, and dose proportionality of cefepime were evaluated in healthy male subjects after single (250, 500, 1000, or 2000 mg) and multiple (1000 mg every 12 hours for 10 days) intramuscular injections. Safety and tolerance were also monitored. High performance liquid chromatography/UV methodology was used to determine cefepime concentrations in plasma and urine. Key pharmacokinetic parameters were determined using noncompartmental methods. Cefepime was absorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 20 publications
3
25
1
1
Order By: Relevance
“…The current study showed that the pharmacokinetic parameters for the test formulation, Cefamax, and the reference formulation, Maxipime, are not significantly different, except for CL The pharmacokinetic parameters for Cefamax obtained from the current study were higher than the results from a previous study [2,5,6], which may be the result of the lower body weight of the volunteers in this study. Thus, the drug concentrations of Cefamax were higher than recommended levels for treatment of the infections for which this substance is approved.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The current study showed that the pharmacokinetic parameters for the test formulation, Cefamax, and the reference formulation, Maxipime, are not significantly different, except for CL The pharmacokinetic parameters for Cefamax obtained from the current study were higher than the results from a previous study [2,5,6], which may be the result of the lower body weight of the volunteers in this study. Thus, the drug concentrations of Cefamax were higher than recommended levels for treatment of the infections for which this substance is approved.…”
Section: Discussioncontrasting
confidence: 71%
“…All subjects had good tolerance and no serious adverse events were observed. Conclusion: Cefamax 1 g intramuscular formulation is bioequivalent to Maxipime 1 g intramuscular formulation based on 90% CIs for C max, AUC [0][1][2][3][4][5][6][7][8][9][10][11][12] , and AUC 0-∞ within 80%-125%. …”
mentioning
confidence: 99%
“…The adverse effects referring to the central nervous system were atypical for this class of substances (13,15,37,39). Only local and peripheral reactions (flush at the puncture site and itching eyes and nose) were probably drug related, because they were recorded during or directly after the 20-min infusion, and they are well-known adverse effects of cephalosporins (1,4,14,38). Also, a well-known rare side effect of cephalosporins is the drug-induced exanthema that appeared 2 and 9 days, respectively, after infusion of ceftazidime and SCE-2787 in one subject (3,22,24,36,46).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the CLR of cefepime, like that of ceftazidime (16,26), occurs by glomerular filtration, with negligible tubular secretion (1,3,5). A drug disposition study using radiolabeled cefepime clearly indicated that this cephalosporin undergoes minimal metabolism and is excreted primarily as an unchanged drug in urine in humans with normal kidney functions (4).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, cefepime has shown excellent efficacy in treating experimental bacteremia and meningitis caused by Escherichia coli, group B streptococci (19), and pneumococci (29). The excellent spectrum of cefepime, its resistance to the Cefepime is cleared primarily by urinary excretion in unchanged form in animals (2, 10, 11) and humans (1,(3)(4)(5). In the single-dose phase I evaluation, limited blood samples were obtained for the preliminary assessment of pharmacokinetics (1).…”
mentioning
confidence: 99%